Novel Bifunctional Acylase from Actinoplanes utahensis: A Versatile Enzyme to Synthesize Antimicrobial Compounds and Use in Quorum Quenching Processes - Lara Serrano-Aguirre; Rodrigo Velasco-Bucheli; Begoña García-Álvarez; Ana Saborido; Miguel Arroyo; Isabel de la Mata (MDPI AG, 2021)
Many intercellular communication processes, known as quorum sensing (QS), are regulated by the autoinducers N-acyl-l-homoserine lactones (AHLs) in Gram-negative bacteria. The inactivation of these QS processes using different quorum quenching (QQ) strategies, such as enzymatic degradation of the autoinducers or the receptor blocking with non-active analogs, could be the basis for the development of new antimicrobials. This study details the heterologous expression, purification, and characterization of a novel N-acylhomoserine lactone acylase from Actinoplanes utahensis NRRL 12052 (AuAHLA), which can hydrolyze different natural penicillins and N-acyl-homoserine lactones (with or without 3-oxo substitution), as well as synthesize them. Kinetic parameters for the hydrolysis of a broad range of substrates have shown that AuAHLA prefers penicillin V, followed by C12-HSL. In addition, AuAHLA inhibits the production of violacein by Chromobacterium violaceum CV026, confirming its potential use as a QQ agent. Noteworthy, AuAHLA is also able to efficiently synthesize penicillin V, besides natural AHLs and phenoxyacetyl-homoserine lactone (POHL), a non-natural analog of AHLs that could be used to block QS receptors and inhibit signal of autoinducers, being the first reported AHL acylase capable of synthesizing AHLs.